Leiomyomatosis Peritonealis Disseminata with Sarcomatous Transformation: A Rare Case Report and Literature Review - Song Xu; Jing Qian (Case Reports in Obstetrics and Gynecology)
Leiomyomatosis Peritonealis Disseminata (LPD) is an uncommon disease characterized by presence of Multiple Leiomyomas in the abdominal and pelvic cavity. Increasingly, literature supports that LPD is an iatrogenic condition. Malignant transformation of LPD is rarely reported. We hereby report a case of a middle-aged female patient who was diagnosed with malignant sarcomatous degeneration in LPD. Gynecologists may get inspiration from this case report.